THE İMPACT OF UZBEKİSTAN'S SOVEREİGN WEALTH FUNDS ON ECONOMİC GROWTH - I. T. Jumaniyazov; A. Khaydarov (American Journals Publishing, 2023)
In developed and developing countries the economic growth of the state depends on many factors. One of the institutions that have an impact on the economy is Sovereign wealth fund. These types of funds have different and at the same time similar objectives. This paper studies the activity of one of those Sovereign wealth fund i.e. the Uzbekistan Reconstruction and Development Fund, established in 2006. It analyzes the significance of the fund’s expenditure in the economic growth of Uzbekistan. The study shows that fund’s expenditure has positive correlation with GDP growth of the country. According to regression analysis, expenditure of the fund is significant variable for the GDP growth of Uzbekistan. Moreover it analyzes some Asian countries’ experience and develops conclusions and proposals on the improvement of Uzbekistan Reconstruction and Development Fund.
Keywords: Sovereign wealth fund, Uzbekistan Reconstruction and Development Fund, GDP growth, expenditure, Uzbekistan